Qualitative and Quantitative Analysis of Phenolic Compounds in Spray-Dried Olive Mill Wastewater - Benincasa, Cinzia; Pellegrino, Massimiliano; Romano, Elvira; Claps, Salvatore; Fallara, Carmelo; Perri, Enzo (Frontiers in Nutrition, 2022)
The processing of olives for oil production generates the most abundant agro-industrial by-products in the Mediterranean area. The three-phase olive oil extraction process requires the addition of a large amount of water to the system, which is difficult to dispose of for its load of toxic pollutants. On the other hand, olive mill wastewater is a rich source of bioactive substances with various biological properties that can be used as ingredients in the food industry for obtaining functional and nutraceutical foods as well as in the pharmaceutical industry. In this study, we present the results relative to the phenolic compounds detected in dried olive mill wastewaters obtained using a spray dryer. Qualitative and quantitative analyses were obtained by high-pressure liquid chromatography–tandem mass spectrometry (HPLC–MS/MS). In particular, the compounds here discussed are: apigenin (9.55 mg/kg dry weight), caffeic acid (2.89 mg/kg dry weight), catecol (6.12 mg/kg dry weight), p-cumaric acid (5.01 mg/kg dry weight), diosmetin (3.58 mg/kg dry weight), hydroxytyrosol (1.481 mg/kg dry weight), hydroxytyrosyl oleate (564 mg/kg dry weight), luteolin (62.38 mg/kg dry weight), luteolin-7-O-glucoside (88.55 mg/kg dry weight), luteolin-4-O-glucoside (11.48 mg/kg dry weight), oleuropein (103 mg/kg dry weight), rutin (48.52 mg/kg dry weight), tyrosol (2043 mg/kg dry weight), vanillin (27.70 mg/kg dry weight), and verbascoside (700 mg/kg dry weight). The results obtained highlighted that the use of dehumidified air as a drying medium, with the addition of maltodextrin, appears to be an effective way to produce a phenol-rich powder to be included in food formulations as well as in pharmaceutical preparations having different biological properties.